Analysis and Design of Multirate Synchronous Sampling Schemes for Sparse Multiband Signals - M. Elena Domínguez-Jiménez; Nuria González-Prelcic (European Signal Processing Conference (EUSIPCO 2012), 2012)
We consider the problem of developing efﬁcient sampling schemes for multiband sparse signals. Previous results on multicoset sampling implementations that lead to universal sampling patterns (which guarantee perfect reconstruction), are based on a set of appropriate interleaved analog to digital converters, all of them operating at the same sampling frequency. In this paper we propose an alternative multirate synchronous implementation of multicoset codes, that is, all the analog to digital converters in the sampling scheme operate at different sampling frequencies, without need of introducing any delay. The interleaving is achieved through the usage of different rates, whose sum is signiﬁcantly lower than the Nyquist rate of the multiband signal. To obtain universal patterns the sampling matrix is formulated and analyzed. Appropriate choices of the parameters, that is the block length and the sampling rates, are also proposed
Keywords: compressive sampling; Kruskal rank; multiband sparse signal; Multicoset sampling; multirate sampling; universal pattern